2014
DOI: 10.1155/2014/704836
|View full text |Cite
|
Sign up to set email alerts
|

Signalment and Blood Types in Cats Being Evaluated as Blood Donors at Two Italian University Blood Banks

Abstract: Data from potential feline blood donors presented at two university blood banks in Italy were recorded. Blood typing was performed using an immunochromatographic method. Over the three years of the study 357 cats representing 15 breeds, 45.3% female and 54.7% male, with a mean age of 3.8 years were evaluated. Of these 90.5% were blood type A, 5.6% type B, and 3.9% type AB. The majority of the cats (54.6%) were European DSH (92.3% were type A, 5.1% type B, and 2.6% type AB), and 21% were Maine Coon (MCO) cats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 12 publications
5
17
1
1
Order By: Relevance
“…To the author’s knowledge, this result is similar to that reported in most other studies with the exception of Portugal, Germany, and UK where a frequency of 6.3%, 7.4%, and 8.5% in mixed breed cats was reported, respectively [ 8 , 17 , 25 ]. Furthermore, the results reported in the present study are similar to those blood types found in feline populations tested in other areas of Italy, with the exception of type AB group [ 13 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…To the author’s knowledge, this result is similar to that reported in most other studies with the exception of Portugal, Germany, and UK where a frequency of 6.3%, 7.4%, and 8.5% in mixed breed cats was reported, respectively [ 8 , 17 , 25 ]. Furthermore, the results reported in the present study are similar to those blood types found in feline populations tested in other areas of Italy, with the exception of type AB group [ 13 , 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…As reported in Table 1 , in this survey the frequency of type B in the feline population is higher (7.0%) compared to most other European studies (i.e., Croatia, Denmark, Finland, Hungary, Iberian Peninsula, Switzerland, and UK) [ 2 , 3 , 5 , 10 , 11 , 17 , 18 , 19 , 21 ] and is comparable to those of four studies conducted in Northern Italy, where about a total of 600 European domestic shorthair cats were enrolled [ 13 , 14 , 15 , 16 ]. Instead, Giger et al and Spada et al reported a high prevalence of blood type B in Central (11.2% in Tuscany region) and Southern Italy (12.1% in Sicily), respectively [ 5 , 16 ].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Em gatos o grupo sanguíneo AB é constituído por três tipos sanguíneos denominados A, B e AB (Spada et al, 2014). Porém, Weinstein et al (2007), detectaram a existência de outro fator sanguíneo, denominado "fator Mik".…”
Section: Introductionunclassified